JavaFX A Beginners Guide - DiMarzio, J. F (McGraw Hill Computing, 2011)
Essential Skills--Made EasyCreate immersive, interactive environments for any platform. JavaFX: A Beginner's Guide starts by explaining the technology behind JavaFX and quickly moves on to installing the JavaFX development environment and tools, including the JavaFX SDK, the Java SE JDK, and NetBeans. Then, you'll learn how to develop desktop, browser, and mobile applications with ease. The book covers effects and transformations, animation, events, and Swing components. Techniques for creating custom modes, embedding video and music, using JavaFX layouts, and styling with CSS are also discussed. Get started using JavaFX right away with help from this fast-paced tutorial.Designed for Easy Learning:Key Skills & Concepts--Chapter-opening lists of specific skills covered in the chapterAsk the Expert--Q&A sections filled with bonus information and helpful tipsTry This--Hands-on exercises that show you how to apply your skillsNotes--Extra information related to the topic being coveredTips--Helpful reminders or alternate ways of doing thingsAnnotated Syntax--Example code with commentary that describes the programming techniques being illustrated